Análisis del proceso del régimen aduanero transbordo que la empresa LIMPAO S.A debe aplicar en su operación. - Rueda Granda, Mayra Lisseth (My University, 2018)
International trade favors the exchange of goods and services between nations that are directed to comply with customs processes through the established laws in force. Analyzing the situation of the company Limpao S.A that is dedicated to the commercialization of cleaning articles will be implemented the transshipment regime to facilitate the realization of the export. In the development of the investigation contents are included based on the object of study that is related to the problem and the determination of the process through the application of the adequate regime to transport the merchandise and the documents that will serve as sustenance before the customs authority; applying the processes and laws that must be followed to perform the operation. It is important to know that the regime is fulfilled in different modes and means of transport such as land, sea and air; especially the operations are carried out through compliance with customs regulations with the application of the process of moving the merchandise from the bulk carrier to a panamax vessel, both are large but the difference preexists in design to the corresponding dimensions in the Panama Canal; container ships are the most common in performing navigation transit. Finally, it is defines operational process that the company must apply for the maritime transshipment of the merchandise, using another ship to embark, through the intervention of the pertinent customs controls; complying with the established laws and in case of non-compliance the respective sactions are applied.
El comercio internacional favorece el intercambio de bienes y servicios entre las naciones que están dirigidas a cumplir con los procesos aduaneros a través de las leyes vigentes establecidas. Analizando la situación de la empresa Limpao S.A. que se dedica a la comercialización de artículos de limpieza se implementara el régimen de transbordo para facilitar la realización de la exportación. En el desarrollo de la investigación se incluyen contenidos basados en el objeto de estudio que se relaciona con el problema y la determinación del proceso mediante la aplicación del régimen adecuado para transportar la mercancía y los documentos que servirán como sustento ante la autoridad aduanera, aplicando las leyes que se deben seguir para realizar la operación. Es importante saber que el régimen se cumple en diferentes modalidades y medios de transporte como terrestre, marítimo y aéreo; especialmente las operaciones se realizan a través del cumplimiento de la normativa aduanera con la aplicación del proceso de traslado de la mercancía desde un buque granelero a un buque panamax; ambos son grandes pero la diferencia se preexiste en el diseño a las dimensiones que corresponde en las esclusa del canal de Panamá; los portacontenedores son los más comunes en realizar el tránsito de navegación. Finalmente se define el proceso operacional que la empresa debe aplicar para el transbordo marítimo de la mercancía, utilizando otro buque para embarcar, mediante la intervención de los controles aduaneros pertinentes; cumpliéndose con las leyes establecidas y en caso de incumplimiento se aplican las sanciones respectivas.
Keywords: ADUANA; COMERCIO INTERNACIONAL; EXPORTACIÓN; TRANSPORTE MARÍTIMO; RÉGIMEN ADUANERO; RÉGIMEN TRANSBORDO